Materiales didácticos en la enseñanza semipresencial y el aprendizaje de matemática en niños de la Institución Educativa Inicial N° 311 San Pablo de Loreto, distrito de San Pablo 2022 - Garcia Vela, Adela Milagros (2023)
This research has been developed with the purpose of arguing the relationship of teaching materials in blended learning and mathematics learning in children of the Initial Educational Institution No. 311 San Pablo de Loreto district of San Pablo 2022. The research is of a relational type, with a correlational and cross-sectional design. The population is all four-year-old children of the Initial Educational Institution No. 311 San Pablo de Loreto. The sample of this research will be 100 children, where non-probabilistic convenience sampling will be used. Observation was used as a technique and an observation guide as an instrument to obtain the data, as well as the questionnaire, the instruments were previously validated through expert judgment. The conclusion There is no significant relationship between the didactic materials in blended teaching and the learning of mathematics in children of the Initial Educational Institution No. 311 San Pablo de Loreto district of San Pablo 2022"